2012
DOI: 10.1088/0953-8984/25/5/056001
|View full text |Cite
|
Sign up to set email alerts
|

The magnetocaloric effect and critical behaviour of the Mn0.94Ti0.06CoGe alloy

Abstract: (2013). The magnetocaloric effect and critical behaviour of the Mn0.94Ti0.06CoGe alloy. Journal Of Physics-Condensed Matter, 25 (5), 1-7.The magnetocaloric effect and critical behaviour of the Mn0.94Ti0.06CoGe alloy AbstractStructural, magnetic and magnetocaloric properties of the Mn0.94Ti0.06CoGe alloy have been investigated using x-ray diffraction, DC magnetization and neutron diffraction measurements. Two phase transitions have been detected, at T-str = 235 K and T-C = 270 K. A giant magnetocaloric effect h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 35 publications
1
17
0
1
Order By: Relevance
“…For the Mn0.96Fe0.04CoGe sample, two changes are observed in the magnetisation curve ( [25]. In the case of Mn0.94Ti0.06CoGe, the transition temperatures were TC hex ~270 K and TM ~235 K. In both samples, substitution for Mn drives the martensitic transformation temperature TM below the Curie temperature of the hexagonal structure TC hex .…”
Section: Magnetisation and Partial Magnetic Phase Diagrammentioning
confidence: 99%
See 1 more Smart Citation
“…For the Mn0.96Fe0.04CoGe sample, two changes are observed in the magnetisation curve ( [25]. In the case of Mn0.94Ti0.06CoGe, the transition temperatures were TC hex ~270 K and TM ~235 K. In both samples, substitution for Mn drives the martensitic transformation temperature TM below the Curie temperature of the hexagonal structure TC hex .…”
Section: Magnetisation and Partial Magnetic Phase Diagrammentioning
confidence: 99%
“…Importantly, the martensitic transformation temperature TM can be tuned easily [12,[22][23][24]. Slight compositional changes, achieved via doping for example [25,26], can stabilise the hexagonal phase to low temperature with a ferromagnetic transition occurring in the hexagonal phase at the Curie temperature TC hex ~275 K [27]. Therefore, if TM is lowered to within the temperature range between TC orth and TC hex , a magneto-structural transition can occur, with potential for an enhanced MCE.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, the magnetic materials with large/giant MCE have been extensively studied experimentally and theoretically due to the high efficiency and eco-friendliness of magnetic refrigeration compared to the commonly used gas compression technique. [1][2][3][4][5][6][7][8] The isothermal magnetic entropy change (ÀDS M ) or adiabatic temperature change (DT ad ) under a varying magnetic field is the key performance indicator of magnetic cooling materials. Searching for magnetic materials with large values of ÀDS M /DT ad has been considered as the main task in this field during the last few years.…”
mentioning
confidence: 99%
“…Importantly, the value of T str depends strongly on several factors including: external pressure, 8 the vacancies in the Co and Mn sites, as well as variation in chemical environment due to element substitution on Mn, Co, or Ge sites. [9][10][11][12][13][14][15][16][17] Recently, MnCoGebased compounds have attracted significant attention; [9][10][11][12][13][14][15][16][17] this is due mainly to the strong coupling between magnetism and structure in these materials. This coupling in turn can lead to MnCoGe-based materials, which exhibit large entropy changes and associated magnetocaloric effects, thereby offering scope for magnetic refrigeration around room temperature.…”
mentioning
confidence: 99%
“…In order to achieve coincidence of magnetic and structural transitions which differ by around 300 K in the parent MnCoGe compound, several approaches to modify the Mn environments have been adopted. [9][10][11][12][13][14][15][16][17] Several studies concerning substitution of other elements for Mn, Co, or Ge have been reported in order to shift and thereby control the transition temperatures T str and T C . [9][10][11][12][13][14] The general aim of such studies is to cause the magnetic and structural transitions to coincide or overlap closely and thereby capitalise on both the magnetic and structural entropies at the resultant magnetostructural transition.…”
mentioning
confidence: 99%